Can foliar application of soluble monoammonium phosphate effectively alleviate herbicide-induced oxidative stress in key crops? - Viveiros, Josiane; Moretti, Luiz Gustavo; Alves Filho, Israel; Pacola, Marcela; Jacomassi, Lucas Moraes; Rodrigues, Vitor Alves; Jamal, Amine; Bossolani, João William; Portugal, José Roberto; Carbonari, Caio Antonio; Crusciol, Carlos Alexandre Costa (Frontiers in Plant Science, 2025)
Phosphorus (P) and nitrogen (N) directly impact final crop productivity by playing essential roles in photosynthesis, ATP formation, carbon assimilation, cell division, and transport. Compared with nutrient application to soil, the nutrients are applied directly to leaves provides a faster response because the nutrients enter plant metabolism more quickly. Foliar fertilization with nutritional supplements can intend to increase crop yields, and little is known about its ability to reduce oxidative stress. This study evaluated the effects of foliar fertilization on crop recovery from phytotoxicity induced by herbicide exposure. Phytotoxicity was induced in soybean, maize, and cotton plants by applying the herbicide carfentrazone-ethyl (at V3, V3 and V4 growth stages, respectively), which induces the accumulation of reactive oxygen species in the cytoplasm, leading to membrane rupture and the appearance of chlorotic spots on leaves. Phytotoxicity induction was followed by the foliar application of monoammonium phosphate (MAP) as a source of N and P. Leaf nutrient content, gas exchange performance, pigment content, photosynthetic enzyme activity, antioxidant metabolism, oxidative stress, proline content, metabolite content, and biometric parameters were evaluated. MAP supplementation increased chlorophyll content, and RuBisCO activity by up to 20.5% (maize) and 16.2% (cotton), respectively, resulting in higher net photosynthetic rates (26.3%; cotton), stomatal conductance (45.7%; cotton), water use efficiency (35.6%; cotton), and carboxylation efficiency (45%; cotton). The activities of antioxidant enzymes also increased, and the concentrations of oxidative stress indicators decreased (H2O2: 33.7% and MDA: 28.3%; soybean). Furthermore, the productivity of all three crops increased, suggesting that foliar application of MAP is an efficient strategy for attenuating phytotoxicity symptoms in crops.